IL-10 underlies distinct susceptibility of BALB/c and C57BL/6 mice to Mycobacterium avium infection and influences efficacy of antibiotic therapy - Susana Roque (2007)
Increased production of IL-10 has been frequently associated with augmented susceptibility to infection. However, the correlation between IL-10 activity and susceptibility to mycobacterial infection is still uncertain. Although studies using transgenic mice overexpressing IL-10 consistently showed an increased susceptibility to mycobacterial infection, experimental approaches in, which IL-10 activity was reduced or abrogated originated inconclusive data. We show here that this controversy might be due to the mouse strains used in the various experimental procedures. Our results show that BALB/c mice are more susceptible than C57BL/6 to Mycobacterium avium infection. This increased susceptibility of BALB/c mice is, to a great extent, due to distinct activity of IL-10 between the two mouse strains. In accordance, reduction of IL-10 activity through the administration of anti-IL-10R mAb, or the absence of IL-10 as studied in IL-10 knockout mice, clearly decreased the susceptibility of BALB/c mice to M. avium but had a less obvious effect in C57BL/6 mice. Moreover, abrogation of IL-10 activity in infected BALB/c mice increased the efficacy of antimycobacterial therapy, whereas for the C57BL/6 mice it produced no effect. These observations show that the activity of IL-10 in response to the same mycobacterial stimulus influences not only the susceptibility to infection but also the efficacy of antimycobacterial therapy. This should now be considered in the context of human response to mycobacterial infection, particularly as a possible strategy to improve treatment against infections by mycobacteria.